The Influence of Financial Performance on CSR in English League Football Clubs - Kusumawardhani, Adhityawati; Hadinata, Christian; Marchyta, Nony Kezia (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
This research seeks to find out if there is a relationship between corporate social responsibility (CSR) and financial performance as measured by return on assets, debt equity ratio, and the current ratio. The primary focus of this work is on the 25 English Premier League clubs that were registered with the Charity Commission UK from 2018 to 2021. Corporate Social Responsibility (CSR) is the independent (explanatory) variable, while Return on Assets (ROA), Debt Equity Ratio (DER), and Current Ratio (CR) are the dependent variables. Regression multivariate modeling is the technique of choice. DER and ROA are found to positively influence CSR, while CR is found to have no impact. The report asserts that stronger clubs have higher financial social responsibility expenditures than weaker clubs. This research contributes new content on the subject of corporate social responsibility (CSR) in the field of sports with particular emphasis on football and provides important guidance to club managers on how to combine finance and CSR strategies.